30-year trends in major cardiovascular risk factors in the Czech population, Czech MONICA and Czech post-MONICA, 1985 - 2016/17 - Cífková, Renata; Bruthans, Jan; Wohlfahrt, Peter; Krajčoviechová, Alena; Šulc, Pavel; Jozífová, Marie; Eremiášová, Lenka; Pudil, Jan; Linhart, Aleš; Widimský, Jiří; Filipovský, Jan; Mayer, Otto; et al. (PloS one, 2020)
BACKGROUND: Compared with Western Europe, the decline in cardiovascular (CV) mortality has been delayed in former communist countries in Europe, including the Czech Republic. We have assessed longitudinal trends in major CV risk factors in the Czech Republic from 1985 to 2016/17, covering the transition from the totalitarian regime to democracy. METHODS: There were 7 independent cross-sectional surveys for major CV risk factors conducted in the Czech Republic in the same 6 country districts within the WHO MONICA Project (1985, 1988, 1992) and the Czech post-MONICA study (1997/98, 2000/01, 2007/08 and 2016/2017), including a total of 7,606 males and 8,050 females. The population samples were randomly selected (1%, aged 25-64 years). RESULTS: Over the period of 31/32 years, there was a significant decrease in the prevalence of smoking in males (from 45.0% to 23.9%; p < 0.001) and no change in females. BMI increased only in males. Systolic and diastolic blood pressure decreased significantly in both genders, while the prevalence of hypertension declined only in females. Awareness of hypertension, the proportion of individuals treated by antihypertensive drugs and consequently hypertension control improved in both genders. A substantial decrease in total cholesterol was seen in both sexes (males: from 6.21 ± 1.29 to 5.30 ± 1.05 mmol/L; p < 0.001; females: from 6.18 ± 1.26 to 5.31 ± 1.00 mmol/L; p < 0.001). CONCLUSIONS: The significant improvement in most CV risk factors between 1985 and 2016/17 substantially contributed to the remarkable decrease in CV mortality in the Czech Republic.
Keywords: kardiovaskulární nemoci; Cardiovascular Diseases; Mortality; kouření cigaret; Adult; Antihypertensive Agents; index tělesné hmotnosti; Male; Cigarette Smoking; obezita; Social Change; lidé; hypercholesterolemie; lidé středního věku; Humans; Body Mass Index; zdravotnické přehledy; Hypercholesterolemia; Middle Aged; antihypertenziva; morbidita; Hypertension; Health Knowledge, Attitudes, Practice; mortalita; Czech Republic; politika; průřezové studie; hypertenze; mužské pohlaví; rizikové faktory; Obesity; dospělí; zdraví - znalosti, postoje, praxe; sociální změna; Politics; Morbidity; Cross-Sectional Studies; Česká republika; ženské pohlaví; Health Surveys; Female; Risk Factors